The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1086/597551
|View full text |Cite
|
Sign up to set email alerts
|

L-Band Spectra of 13 Outbursting Be Stars

Abstract: We present new L-band spectra of 13 outbursting Be stars obtained with ISAAC at the ESO Paranal observatory. These stars can be classified in three groups depending on the presence/absence of emission lines and the strength of Brα and Pfγ emission lines relative to those of Humphreys lines from transitions 6-14 to the end of the series. These groups are representative of circumstellar envelopes with different optical depths. For the group showing Brα and Pfγ lines stronger than Humphreys lines, the Humphreys d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
29

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(73 citation statements)
references
References 36 publications
2
42
0
29
Order By: Relevance
“…Mennickent et al (2009) and Granada, Arias, & Cidale (2010) analyzed independently L-band spectra of different samples of outbursting Galactic Be stars. They found changes in the optical density of the CDDs that could be consistent with the model proposed by de Wit et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mennickent et al (2009) and Granada, Arias, & Cidale (2010) analyzed independently L-band spectra of different samples of outbursting Galactic Be stars. They found changes in the optical density of the CDDs that could be consistent with the model proposed by de Wit et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Their profiles are sensitive to the physical properties and dynamical structure of the line-forming regions and thus become useful probes of circumstellar environments. An inspection of the L-band hydrogen spectra of Be stars allows a classification in three groups following Mennickent et al (2009): Group I contains the stars with Brα and Pfγ equally intense as Hu lines, Group II consists of those with Brα and Pfγ more intense than Hu lines, and Group III is made up of those with no detected emission. This classification scheme reflects the optical depth conditions in the Be star envelope.…”
Section: Introductionmentioning
confidence: 99%
“…We describe the behaviour of IR hydrogen emission lines of a sample of Be stars and discuss the physical properties of the circumstellar envelopes of Be stars classified in Groups I and II (Mennickent et al 2009). We find that while Humphreys and Pfund lines of Group I stars form in an optically thick envelope/disk, Group II stars show Pfund lines that form in an optically thick medium and Humphreys lines originating in optically thinner regions.…”
mentioning
confidence: 99%
“…The same kind of variable stars were found in the Large Magellanic Cloud (Sabogal et al 2005) and in the direction of the Galactic Bulge (Sabogal et al 2008). Samples of Type-1 stars were studied by de Wit et al (2006) and by Mennickent et al (2009). These studies showed that Type-1 stars could be stars with an optically thick circumstellar envelope that evolves in an optically thin one before to dissipate into the interstellar medium.…”
Section: Introductionmentioning
confidence: 72%